Penerapan Strategi Active Learning Tipe Everyone is A Teacher Here untuk Meningkatkan Hasil Belajar Biologi Siswa pada Materi Masalah Lingkungan - Fajar Permana; Hadi Pramono (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2021)
An interesting learning strategy that triggers students to be bold in expressing their ideas, namely the Active Learning Strategy. The research objectives were to determine (1) the application of the Active Learning strategy type Everyone is A Teacher Here, (2) the difference in biology learning outcomes between students who applied the “Everyone is A Teacher Here type of Active Learning strategy using animated videos and lectures, and (3) response students towards the implementation of the Active Learning strategy type Everyone is A Teacher Here. Data collection techniques used were tests, observations, and questionnaires. The research sample was students of class X-8 (experimental class) and class X-5 (control class) MAN Cirebon 1, using purposive sampling. Data analysis used T test. The results of the study were (1) student activity increased after implementing the Active Learning strategy type Everyone is A Teacher Here using animated video, was in the good category (30,54%), (2) there was a difference in the improvement of learning outcomes between students who apply the Active Learning strategy type Everyone is A Teacher Here using animated videos and lectures, (3) student responses to the Active Learning strategy type Everyone is A Teacher Here is in the strong category (75,90%).